2010
DOI: 10.1590/s0103-84782010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas de Psidium guajava L. 'Século XXI' tratadas com ácido indolbutírico veiculado em talco e álcool

Abstract: Na produção comercial de Psidium guajava L. (goiabeira), a qualidade das mudas é de fundamental importância, a fim de garantir a homogeneidade, a rápida formação, a alta produtividade e o início precoce da produção, tornando-se imprescindível a utilização da propagação assexuada. O objetivo deste trabalho foi avaliar o enraizamento de estacas de Psidium guajava L. 'Século XXI' tratadas com diferentes concentrações de ácido indolbutírico (AIB) veiculados em talco e álcool. Foram utilizadas estacas herbáceas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
3
18
0
12
Order By: Relevance
“…In herbaceous cuttings of guava (Psidium guajava L.), it was found that the IBA dose of 2,000 mg L -1 was the most effective for rooting (28.5%) (YAMAMOTO et al, 2010). This was similar to the results obtained in this work, in which the same dose, although without presenting a statistical difference, obtained the highest rooting (36.25%).…”
Section: Ornamental Horticulturesupporting
confidence: 88%
See 2 more Smart Citations
“…In herbaceous cuttings of guava (Psidium guajava L.), it was found that the IBA dose of 2,000 mg L -1 was the most effective for rooting (28.5%) (YAMAMOTO et al, 2010). This was similar to the results obtained in this work, in which the same dose, although without presenting a statistical difference, obtained the highest rooting (36.25%).…”
Section: Ornamental Horticulturesupporting
confidence: 88%
“…In guava (P. guajava), the highest dose of IBA tested (2,000 mg L -1 ) provided the highest number of roots per cutting and the highest root dry matter (YAMAMOTO et al, 2010). ZIETEMANN and ROBERTO (2007) found similar results for the same species, in which 1,500 and 2,000 mg L -1 IBA doses provided greater rooting, number of roots, length and root dry mass.…”
Section: Ornamental Horticulturementioning
confidence: 84%
See 1 more Smart Citation
“…It also prevents desiccation of the base of cuttings and possesses pore space which facilitates the availability of oxygen to the roots and doesn't have any phytotoxic substances for the plants FACHINELLO et al, 2005). Among the substrates commonly used for fruit plants propagation, some can be listed, such as vermiculite, rice husk and coconut fi ber (ZIETEMANN & ROBERTO, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, em outras espécies, como em Psidium guajava L. cv. Século XXI (Yamamoto et al, 2010) e Ginkgo biloba L. (Bitencourt et al, 2010), a veiculação do AIB em talco é mais eficiente que em solução hidroalcoólica. Por outro lado, em mirtileiro cvs.…”
Section: Resultsunclassified